2022
DOI: 10.3390/s22020596
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Heavy Metal Ion Detection Using Surface-Enhanced Raman Spectroscopy

Abstract: Surface-Enhanced Raman Spectroscopy (SERS) is often used for heavy metal ion detection. However, large variations in signal strength, spectral profile, and nonlinearity of measurements often cause problems that produce varying results. It raises concerns about the reproducibility of the results. Consequently, the manual classification of the SERS spectrum requires carefully controlled experimentation that further hinders the large-scale adaptation. Recent advances in machine learning offer decent opportunities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Based on the current reported work, the benefits of machine learning for SERS and SEIRA can be summarized as follows. 45,112–125…”
Section: Concept Of Machine Learning Enhancing Sers and Seiramentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the current reported work, the benefits of machine learning for SERS and SEIRA can be summarized as follows. 45,112–125…”
Section: Concept Of Machine Learning Enhancing Sers and Seiramentioning
confidence: 99%
“…Based on the current reported work, the benefits of machine learning for SERS and SEIRA can be summarized as follows. 45,[112][113][114][115][116][117][118][119][120][121][122][123][124][125] Machine learning algorithms enable the automated design of SERS/SEIRA substrates to avoid time-consuming and onerous design processes. Taking SEIRA's antenna design as an example, 126 its first step is to analyze the infrared spectrum of the analyte molecule and obtain the position of the molecular vibration.…”
mentioning
confidence: 99%
“…Similar to other popular preprocessing techniques, e.g., baseline correction and power-spectral normalization, it is possible to combine MVNet with neural network-based regression models. 18,19 In such an end-to-end deep learning framework, one can predict the concentration of an unseen target analyte without any preprocessing. This is a particularly attractive feature for solving the reproducibility issues in quantitative SERS measurements.…”
Section: Implications Of the Studymentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Although these studies have mainly focused on building application-specific predictive models, some studies have suggested methods to improve the consistency of predictive performance under independent test conditions. 18,19 In addition, Liu et al 20 proposed a convolutional neural network (CNN)-based unified solution for Raman signal analysis. Park et al 21 also proposed a pseudosiamese network to identify the best matching signal from reference spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods have high detection accuracy, they are time-consuming, laborious, complicated sample pretreatment and have a limited detection range, which cannot meet the requirements of green, rapid, and large-scale detection ( Bian et al., 2020 ; Shojaei et al., 2021 ; Zhao et al., 2021 ). Recently, with the development of optical instruments and machine learning, the sensitivity of optical imaging spectroscopy has been improved and gradually applied to the detection of heavy metals for plants because of the simple, rapid, and in situ advantages provided by spectroscopy ( Zhou et al., 2020a ; Park et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%